Resistance transferance of Amorimia septentrionalis poisoning in goats by ruminal transferance fluid from goats with induced resistance by the inoculation of sodium monofluoroacetate-degrading bacteria - Layze Cilmara Alves da Silva (Ciência Rural, 2015)
Amorimia septentrionalis is a sodium monofluoroacetate (MFA) - containing plant that causes sudden death in ruminants. The aim of this study was to determine whether the resistance to A. septentrionalis poisoning in goats conferred by the intra-ruminal inoculation with the MFA-degrading bacteria Ancylobacter dichloromethanicus and Pigmentiphaga kullae can be transferred to susceptible goats by the transfaunation of rumen content. Two groups of 8 goats and 2 goats resistant to A. septentrionalis poisoning were used. Goats in Group 1 received four daily doses of 160ml of rumen content from resistant goats and subsequently ingested 8 daily doses of 5g kg -1 of A. septentrionalis . Goats from Group 2 (control) received only the plant. In Group 1, only 2 goats showed mild tachycardia and mild jugular vein engorgement on the 4 th and 5 th day, but they subsequently returned to normal, even with the continuation of plant administration. All control goats showed severe signs of intoxication and the plant administration was suspended between the 3 rd and 7 th day. So, the transfer of ruminal fluid from goats previously inoculated with MFA-degrading bacteria induces resistance to poisoning by A. septentrionalis in susceptible goats.